Further Reflections on Disentangling Shape and Level Effects in Person-Centered Analyses: An Illustration Exploring the Dimensionality of Psychological Health. Issue 3 (3rd May 2016) - Morin, Alexandre J. S.; Boudrias, Jean-Sébastien; Marsh, Herbert W.; Madore, Isabelle; Desrumaux, Pascale
Abstract : Morin and Marsh (2015) proposed a methodological framework to disentangle shape and level effects in latent profile analyses. We discuss limitations of this framework (based on a logic similar to that of higher-order measurement models), and suggest that these limitations are easily solved by a more thorough examination of the variable-centered measurement models underlying profile indicators. This study presents complementary variable- and person-centered approaches aiming to assess the dimensionality of psychometric constructs. Psychometric measures often assess separate conceptually-related facets of global overarching constructs, based on the assumption that these overarching constructs exist as global entities including specificities mapped by the facets. The framework proposed here explicitly models this dimensionality in both variable- and person-centered analyses. To illustrate this revised psychometric framework, we use ratings of psychological health collected from 1, 232 teachers, and show how this revised framework provides a clearer picture of teachers' profiles of psychological health.